Knock Out of miRNA-30a-5p and Reconstitution of the Actin Network Dynamics Partly Restores the Impaired Terminal Erythroid Differentiation during Blood Pharming - Thiel, Jessica; Sürün, Duran; Brändle, Desiree C.; Teichert, Madeleine; Künzel, Stephan R.; Friedrich, Ulrike; Dahl, Andreas; Schubert, Kristin; Rzagalinski, Ignacy; Shevchenko, Andrej; Traikov, Sofia; Mirtschink, Peter; et al. (Stem cell reviews and reports, 2025)
In vitro red blood cell (RBC) production offers a promising complement to conventional blood donation, particularly for patients with rare blood types. Previously, we developed imBMEP-A, the first erythroid cell line derived from reticulocyte progenitors, which maintains robust hemoglobin expression and erythroid differentiation in the presence of erythropoietin (EPO) despite its immortalized state. However, clinical translation remains hindered by the inability to scale up production due to impaired in vitro enucleation of RBC progenitor cell lines. Enhancing enucleation efficiency in imBMEP-A cells involved CRISPR/Cas9-mediated knockout (K.O.) of miR-30a-5p, a key enucleation inhibitor, moderately increasing rates to 3.3 ± 0.4%- 8.9 ± 1.7%. Further investigation of enucleation inefficiencies led to transcriptome and proteome comparisons between imBMEP-miR30a-K.O. cells and hematopoietic stem cells (HSCs). These analyses revealed altered gene expression and protein abundances linked to metabolic transitions, apoptosis promotion, and cytoskeletal regulation. Notably, forced expression of the proto-oncogene c-Myc, required for cell immortalization, emerged as a key driver of these physiological changes. Counteracting these effects required optimization of imBMEP-A cells by activating BCL-XL transcription and knocking out SCIN, which encodes the actin-severing protein scinderin. While BCL-XL is upregulated in normal erythropoiesis, it is downregulated in imBMEP-A. Conversely, SCIN, typically absent in erythroid cells, is highly expressed in imBMEP-A, disrupting actin organization. These interventions improved viability, restored actin network formation, and increased terminal erythropoiesis, yielding 22.1 ± 1.7% more orthochromatic erythroblasts. These findings establish a foundation for optimizing imBMEP-A cells for therapeutic use and advancing the understanding the pathophysiology of erythroleukemia.
Online veröffentlicht: 26. August 2025
Gesehen am 18.02.2026